(untitled) (International Journal of Engineering and Computer Science, 2017)
At present cloud computing is going to be very famous technology in IT enterprises. For a company, the data stored is huge and it is very precious. All functions are performed through networks. Thus, it becomes very important to have the secured use of data. Cloud Computing, an emerging computing paradigm, requires additional security which is provided using HASBE and this can emerge as a new security feature for various organizational platforms. We propose attribute based solution so that performance of cloud can be improved. It is implemented using cipher text policy (CP-ABE) by encrypting and decrypting the data in the cloud and makes the data password protected so that the cloud system achieves scalability, flexibility and multi layered security by implementing data owners to share their data with data consumers controlled by the domain authority.